A note on the local injectivity of weakly differentiable mappings having constant Jacobian sign - Cristea, Mihai (MATHEMATICA SCANDINAVICA, 2003)
We give topological and analytical conditions in order that some weakly differentiable mappings with constant Jacobian sign to be locally injective, generalizing results from [10], [2], established for Sobolov mappings.